International Perspectives on Identity and Acculturation in Emerging Adulthood: Introduction to the Special Issue. Issue 1 (February 2018) - Landberg, Monique; Dimitrova, Radosveta; Syed, Moin
This article introduces the special issue, International Perspectives on Identity and Acculturation in Emerging Adulthood . The idea for this issue was put forward by emerging scholars at the 7th Biennial Conference of the Society for the Study of Emerging Adulthood in Miami, FL, in October 2015. This special issue gathers qualitative, quantitative, and mixed methods studies from North America, Europe, and South Africa on identity and acculturation in diverse samples. The five papers seek to shed light on the interplay of ethnicity, identity, and acculturation processes in underresearched contexts, in terms of either country or subpopulations within a country.